Case Report: A case of occupational methyl iodide-induced encephalopathy - Liu, Hongyu; Shang, Ruikai; Tian, Qiaoxin; Liu, Yuru; Jian, Xiangdong (Frontiers in Pharmacology, 2025)
Iodomethane is a commonly used methylation reagent in organic synthesis. However, reports of acute iodomethane poisoning are rare. Herein, we report the successful treatment of a patient with acute iodomethane poisoning. During processing and production, owing to inadequate personal protection, the patient’s eyes were directly exposed to iodomethane gas, leading to blurred vision and magnetic resonance imaging findings consistent with toxic encephalopathy. Following a comprehensive diagnosis and treatment at our hospital, outpatient follow-ups and clinical assessments confirmed the patient’s recovery.